Development and initial evaluation of the athlete eating psychopathology observation questionnaire for sport professionals - Sandgren, S. S.; Haycraft, E.; Plateau, C. R. (Journal of Clinical Sport Psychology, 2023)
Eating psychopathology symptoms are common in athletes; however, it is unknown which symptoms are detected and to what extent by sport professionals. This study aimed to develop and evaluate a self-report questionnaire to explore which features of eating psychopathology in athletes are detected by sport professionals, and how observation of these symptoms might vary. Thirty-one questions were developed and 232 sport professionals (56% male) participated in the study. Exploratory Factor Analysis revealed a 20-item, five-factor solution (Negative Affect, Dieting Practices, Fear of Eating in Social Contexts, Bingeing and Purging, and Compulsive Exercise). Participants most frequently reported observing athletes` dieting practices, while symptoms of a fear of eating in social contexts were observed least frequently. This study has developed and preliminarily tested the Athlete Eating Psychopathology Observation Questionnaire (AEPOQ), which now requires further validation. The findings provide important directions for education initiatives with sport professionals regarding identification of eating psychopathology symptoms.